The Effect of Managerial Sentiment on Market-to-Book Ratio - Myšková, Renáta; Hájek, Petr (My University, 2016)
To be able to properly evaluate the financial performance of the company, not only that we need financial statements, but it is also necessary to provide all stakeholders with further details. In this context, corporate management is increasingly focused on improving the structure and volume of the information contained in annual reports in order to strengthen the company's position among all stakeholders. This article aims to assess the impact of the information published in annual reports of companies on the market value of the shares in the context of the financial value of the enterprise. Considering that from the investor's perspective an investment is assessed in relation to the intrinsic value of the share, a balance model was elected that uses historical prices while being based on information contained in the financial statements. We find inverse effects for negative and positive word lists. Notably, we show that the net optimism in annual reports is perceived positively with stakeholders.
Vliv manažerského sentimentu na ukazatel Market-to-Book Ratio
Keywords: Managerial sentiment; stock market; Market-to-Book-ratio; dividend policy; fundamental analyses; bag-of-words; manažerský sentiment; akciový trh; Market-to-Book-ratio; dividendová politika fundamentální analýza; bag-of-words